2015
DOI: 10.1186/s40152-014-0014-5
|View full text |Cite
|
Sign up to set email alerts
|

Fish commoditization and the historical origins of catching fish for profit

Abstract: Humanity's relationship with fish dates back to prehistory, when ancestral hominins evolved the capacity to exploit aquatic resources. The impacts of early fishing on aquatic ecosystems were likely minimal, as primitive technology was used to harvest fish primarily for food. As fishing technology became more sophisticated and human populations dispersed and expanded, local economies transitioned from hunter-gatherer subsistence to barter and complex trade. This set up a positive feedback ratcheting fishing tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 84 publications
(63 reference statements)
1
34
0
Order By: Relevance
“…Lastly, the long history of commercial fishing across many European countries (including Britain) for G. morhua , C. harengus , S. salar , Acipenser spp., and many other species, creates a shared cultural responsibility for the present state of the seas. It has been observed that both traditional ecological knowledge and learned grassroots ocean literacy can enhance support for careful stewardship of shared natural resources, and vice versa (Drew, ; Engelhard et al, ; Pitcher & Lam, ). In a European context, it will be crucial to the future of aquatic life that we recognise the ecological heritage debt owed for centuries of wealth, sustenance and well‐being.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, the long history of commercial fishing across many European countries (including Britain) for G. morhua , C. harengus , S. salar , Acipenser spp., and many other species, creates a shared cultural responsibility for the present state of the seas. It has been observed that both traditional ecological knowledge and learned grassroots ocean literacy can enhance support for careful stewardship of shared natural resources, and vice versa (Drew, ; Engelhard et al, ; Pitcher & Lam, ). In a European context, it will be crucial to the future of aquatic life that we recognise the ecological heritage debt owed for centuries of wealth, sustenance and well‐being.…”
Section: Discussionmentioning
confidence: 99%
“…Shifts in target species, a classic symptom of serial depletions in modern times (Pitcher & Lam, ), are characteristic of some archaeologically fish‐bone data. This phenomenon can unfold in differing ways.…”
Section: Intensity Of Exploitation and Other Anthropogenic Effectsmentioning
confidence: 99%
“…). As drivers for increased food consumption such as income, urbanization, trade liberalization, food corporations, retailing and marketing (Kearney ), and allied commoditization (Lam and Pitcher ; Pitcher and Lam ), spread from the Western world, pervading other cultures, food consumption and trade will increase.…”
Section: Introductionmentioning
confidence: 99%
“…Here we look back to only 1000 BC (Fig. a); however, prehistoric humans have had an enduring relationship with marine resources (Pitcher and Lam ). Much has been written about fisheries depletion (Pitcher and Cheung ), but our association with fish yields identifies significant long‐term benefits, which, although often compromised by overfishing, continue to flow from over half of the currently assessed populations that are sustainably fished, being rebuilt (Worm et al .…”
Section: Resultsmentioning
confidence: 99%
“…Reconstructions without these additional factors illustrate similar long-term trends in North Sea herring (Pitcher and Lam 2014), but for this work we are interested in more accurate annual herring catch and biomass values.…”
Section: Reconstructing Historical Fish Populationsmentioning
confidence: 99%